Role of exosomes as a proinflammatory mediator in the development of EBV-associated lymphoma - Higuchi, Hiroshi; Yamakawa, Natsuko; Imadome, Ken Ichi; Yahata, Takashi; Kotaki, Ryutaro; Ogata, Jun; Kakizaki, Masatoshi; Fujita, Koji; Lu, Jun; Yokoyama, Kazuaki; Okuyama, Kazuki; Sato, Ai; et al. (American Society of Hematology, 2018)
Epstein-Barr virus (EBV) causes various diseases in the elderly, including B-cell lymphoma such as Hodgkin's lymphoma and diffuse large B-cell lymphoma. Here, we show that EBV acts in trans on noninfected macrophages in the tumor through exosome secretion and augments the development of lymphomas. In a humanized mouse model, the different formation of lymphoproliferative disease (LPD) between 2 EBV strains (Akata and B95-8) was evident. Furthermore, injection of Akata-derived exosomes affected LPD severity, possibly through the regulation of macrophage phenotype in vivo. Exosomes collected from Akata-lymphoblastoid cell lines reportedly contain EBV-derived noncoding RNAs such as BamHI fragment A rightward transcript (BART) micro-RNAs (miRNAs) and EBVencoded RNA.We focused on the exosome-mediated delivery of BART miRNAs. In vitro, BART miRNAs could induce the immune regulatory phenotype in macrophages characterized by the gene expressions of interleukin 10, tumor necrosis factor-a, and arginase 1, suggesting the immune regulatory role of BART miRNAs.The expression level of an EBV-encoded miRNA was strongly linked to the clinical outcomes in elderly patients with diffuse large B-cell lymphoma.These results implicate BART miRNAs as 1 of the factors regulating the severity of lymphoproliferative disease and as a diagnostic marker for EBV1 B-cell lymphoma. (Blood. 2018;131(23):2552-2567).